Strategi Pengurus dalam Menanggulangi Kasus Bullying Santri Pondok Pesantren Miftahul 'Ulum Wonoyoso Kebumen - Niswah, Fina Khoridatun; Mustajab, Mustajab (IAINU Kebumen, 2026)
This Study aims to describe the strategies implemented by the administrators of Pondok Pesantren Miftahul ‘Ulum Wonoyoso Kebumen in addressing bullying among students( santri). Bullying has become a serious concern in islamic boarding schools as it may hinder the mental, social, and spiritual development of the students. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth intervieuws with administrators, caretskers, and students, as well as documentation. The data analysis process consisted of data reduction, data presentation, and drawing conclusions. The findings indicate that bullying at the pesantren occurs in various forms, including verbal, physical, and psychological bullying. The strategies adopted by the administrators include providing individual counseling, fostering moral character through religious activities, enforcing rules and educational sanctions, mediating conflcts among students, and strengthening supervision within the boarding school environment. These strategies were proven effective in reducing the frequency of bullying cases furher recommends enhancing persuarsive approaches and axpanding chararter-building programs as preventive measures for the future.